Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 11878 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Hesperia comma (Linnaeus, 1758)", { "or" : [ "Geometry POLYGON((-26 90,-26 -90,180 -90,180 90,-26 90))", "Geometry POLYGON((-180 90,-180 -90,-169 -90,-169 90,-180 90))" ] }, "HasGeospatialIssue is false" ] } The dataset includes 11878 records from 65 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000145-160118175350007/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences